MODELISASI BIDDING BOX BRIDGE DENGAN MENGGUNAKAN KURVA BEZIER DAN INTERPOLASI LINIER - Anggraeni, Dewi; Juliyanto, Bagus (Jurusan Matematika FMIPA Universitas Jember, 2022)
Bidding Box is used as a place for bridge bid cards with various models. The Bidding Box is made using a technique resulting from the Bezier curves and linear interpolations. This study aims to produce a procedure for how to design various relics in the Bidding Box. This research method is divided into several stages. First, build some basic objects as constituent components of the Bidding Box from beam and rectangular. Next, the procedure for assembling the components of the Bidding Box from the first procedure is on one modeling axis.Keywords : Bidding box, deformation, Bezier curveMSC2020 : 51A05